Estratégias de controle de poluentes gasosos das indústrias do município de Toledo-PR: Técnica do Lean e Seis Sigmaa - Cordeiro Júnior, Joel (2020)
The growing industrialization process increases the generation of various residues, among them, the gaseous residues with particulate solids, which present risk to the population health. In this context, the study aimed to develop pollutant control strategies for industries in the city of Toledo-PR using the Lean and Six Sigma Technique, applied in a case study of a spinning industry. In the first part, the methodology included the survey of sources that generate industrial waste and the quantification of the potential generator of waste in the municipality of Toledo-PR. The second part included the development of strategies by the Lean Six Sigma Technique and application in a spinning company in Toledo-PR. The risk map was presented with georeferenced data from the Toledo-PR industries, for the period from 2018 to 2019. The results point to the generation of 2,926,032,158 ton.year-1 of solid, liquid and gaseous waste. It is estimated that 62.9% of waste underwent treatment. It was also found that the data source of the researched municipalities presents discrepancies in the quantitative records of the registration of transformation industries and of the waste generated. The proposed strategy is tested in the spinning industry and presented satisfactory results and after the adjustments in the production process, the eco-efficiency presented a value of 0.6612 global and Cp and Cpk equal to 1.0 proving the reach of statistical control of the process. In general, the results show that the use of the Lean and Six Sigma philosophy, combined with techniques and tools, for the purpose of clean production, can be implemented in industries in the various sectors of the economy.